Implementation of SIMRS Authorization System in Supporting the Competency Achievement of Poltekkes Kemenkes Tasikmalaya Students - Ida Wahyuni; Dedi Setiadi; Diana Barsasella; Ulfah Fauziah (Poltekkes Kemenkes Tasikmalaya, 2025)
Background: Digital transformation in healthcare is a strategic priority to achieve the National Medium-Term Development Plan (RPJMN) 2025–2045. Hospital Information Systems (SIMRS) play a key role in improving service quality and supporting the competency development of health professionals. However, challenges such as unrestricted access, weak confidentiality culture, and inadequate authorization mechanisms remain critical issues. Objective: This study aimed to examine the implementation of the SIMRS authorization system in supporting clinical practicum competency while ensuring patient data security. Methods: A quantitative cross-sectional design was used, involving 79 practicum students and 8 clinical instructors from 8 hospitals affiliated with Poltekkes Kemenkes Tasikmalaya. Data were collected through structured questionnaires assessing four key variables: access policies, role-based access control (RBAC), data security, and audit trails. Data were analyzed descriptively. Results: Findings showed that access policies and RBAC effectively supported practicum needs by enabling students to access learning modules without altering patient records. However, weaknesses were found in data security, including shared accounts and the absence of confidentiality agreements. Audit trails were functional but weakened by account sharing. Clinical instructors noted positive aspects such as regular policy updates but identified insufficient individual access control. Conclusion: Overall, SIMRS authorization supports clinical competency development. Strengthening data security enforcement, confidentiality agreements, and user accountability is necessary to enhance privacy protection and maintain trust in digital health systems.